Surface Properties of Non-conventional Cellulose Fibres - Sfiligoj Smole, Majda; Hribernik, Silvo; Kurečič, Manja; Urbanek Krajnc, Andreja; Kreže, Tatjana; Stana Kleinschek, Karin (Biobased Polymers, 2019)
The authors describe how sustainable textile fibers from crops such as quinoa, grass, hops, corn and wheat stems, etc. have recently begun to generate great interest. The structure-property relationships of such non-conventional cellulose fibers are studied in this brief, as are their sorption and surface properties which are of primary importance. A systematic review of each fiber's properties is given, the emphasis is placed on the water sorption capacity, the fiber's surface potential, and fibrillation properties.